Sustainability strategy implementation and employee adoption: Case study of a global home furnishing retail chain - Annila, Johanna Vilhelmiina (2024)
This thesis investigates the implementation and adoption of sustainability strategies within a global home furnishing retail chain in Finland, focusing particularly on the challenges and enablers. The theoretical background is rooted in corporate sustainability, emphasizing the urgent need for retail industries to address environmental, social, and economic challenges through effective sustainability strategy implementation. This study integrates concepts from change management and organizational behaviour, examining how these areas intersect to affect strategy implementation at the employee level.